1973
DOI: 10.1063/1.1661876
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxially grown AlN and its optical band gap

Abstract: Single-crystal layers of AlN have been grown on sapphire substrates between 1000 and 1100 °C by vapor-phase reaction of aluminum chlorides with ammonia. The purity, color, crystallinity, growth morphology, and electrical resistivity of the epitaxial layers have been investigated. Infrared specular reflection measurements showed the presence of an appreciable strain at the AIN-sapphire epitaxy interface. Optical absorption data strongly suggest the AlN is a direct band-gap material with a value of about 6.2 eV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
158
2
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 578 publications
(184 citation statements)
references
References 31 publications
14
158
2
2
Order By: Relevance
“…In addition, AlN has a high Debye temperature, 1150 K, 27 which Brgoch et al 9 have shown to be a good indicator of high quantum yield of Ce 3+ in a phosphor host. Further advantages such as excellent thermal shock resistance 10 and large band gap, 6.2 eV, 11 increase the attractiveness of an AlN-based ceramic down-conversion material for LED based white light.…”
Section: © 2016 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…In addition, AlN has a high Debye temperature, 1150 K, 27 which Brgoch et al 9 have shown to be a good indicator of high quantum yield of Ce 3+ in a phosphor host. Further advantages such as excellent thermal shock resistance 10 and large band gap, 6.2 eV, 11 increase the attractiveness of an AlN-based ceramic down-conversion material for LED based white light.…”
Section: © 2016 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…(2), where the band gaps of Sc x Ga 1-x N films have been presented in Ref. 16 and the band gap of AlN have been known as 6.2 eV 13,42 . Therefore, a band alignment diagram can be constructed, as shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…The HRTEM images of the AlN film and sapphire substrate in is also valid for the growth accompanied by the formation of an amorphous interlayer. The relationship has usually been observed for epitaxial growth of AlN on the sapphire substrate without the formation of any amorphous interlayer by using methods such as laser ablation of AlN target, 15) vapor-phase reaction of AlCl 3 with NH 3 , 16) and metalorganic chemical vapor deposition. 17) Vennéguès and Beaumont observed no amorphous interlayer in the nitridation of (0001) sapphire surface by NH 3 and also showed the orientation relationship.…”
Section: )5)mentioning
confidence: 99%